New Editor's Statement - Denson, Eric L. (My University, 1996)
The new editor introduces himself and his vision for the journal as the flagship for the organization and to publish high quality articles that add to the knowledge base, challenge existing opinion, and epxlain the implications of research applied to practice.
Keywords: editorial